Evaluation of a multi-atlas CT synthesis approach for MRI-only radiotherapy treatment planning. (March 2017) - Guerreiro, F.; Burgos, N.; Dunlop, A.; Wong, K.; Petkar, I.; Nutting, C.; Harrington, K.; Bhide, S.; Newbold, K.; Dearnaley, D.; deSouza, N.M.; Morgan, V.A.; et al.
Highlights: Establishing MRI-only RTP workflows requires synthetic CTs for dose calculation. This study evaluates the feasibility of using a multi-atlas CT synthesis approach. The proposed method was validated on head and neck and prostate cancer patients. Results showed an accurate bone estimation for future patient positioning. Results showed that synthetic CTs are suitable to perform clinical dose calculations. Abstract: Background and purpose: Computed tomography (CT) imaging is the current gold standard for radiotherapy treatment planning (RTP). The establishment of a magnetic resonance imaging (MRI) only RTP workflow requires the generation of a synthetic CT (sCT) for dose calculation. This study evaluates the feasibility of using a multi-atlas sCT synthesis approach (sCTa ) for head and neck and prostate patients. Material and methods: The multi-atlas method was based on pairs of non-rigidly aligned MR and CT images. The sCTa was obtained by registering the MRI atlases to the patient's MRI and by fusing the mapped atlases according to morphological similarity to the patient. For comparison, a bulk density assignment approach (sCTbda ) was also evaluated. The sCTbda was obtained by assigning density values to MRI tissue classes (air, bone and soft-tissue). After evaluating the synthesis accuracy of the sCTs (mean absolute error), sCT-based delineations were geometrically compared to the CT-based delineations. Clinical plans were re-calculated on both sCTs and a dose-volume histogram and a gamma analysis was performed using the CT dose as ground truth. Results: Results showed that both sCTs were suitable to perform clinical dose calculations with mean dose differences less than 1% for both the planning target volume and the organs at risk. However, only the sCTa provided an accurate and automatic delineation of bone. Conclusions: Combining MR delineations with our multi-atlas CT synthesis method could enable MRI-only treatment planning and thus improve the dosimetric and geometric accuracy of the treatment, and reduce the number of imaging procedures.